Acute toxicity of saponins from the fruit of bitter apple Citrullus colocynthis (L.) Schrad,on the Norway rat, Rattus norvegicus (Berkenhout) - Alias, Ehab; Zeinelabdin, Mohamed; Bashir, Nabil; Assad, Yousif (Gezira Journal of Agricultural Science, 2015)
Citrullus colocynthis (L.) Schrad (CCT) is an important medicinal plant belonging to the family Cucurbitaceae. It is a well-recognized plant in the traditional medicine and used in rural areas as a purgative, ant diabetic and insecticide. The objective of this study was to evaluate saponins acute toxicity. Crude saponins were extracted from the rind andtheir acute toxicity was determined on Norway rat Rattus norvegicus (Berkenhout). Five dosage levels (60, 70, 80, 90 and 100 mgs saponins/rat) were selected following a pilot study and administered intraperitoneally (I.P.) to each batch of albino rats (4 rats/ batch). The treated rats were observed for 96 hr for acute toxicity symptoms. Death occurred between 1–4 days post- treatment. The corrected mortalities were 0, 25,50,75 and 100%, respectively. The LC 50 was 79.43 mg / rat. Symptoms and behavioural changes during the observation period were anorexia, abnormal gait, twitches, blepharoptosis, reduced activity and bleeding. Severe diarrhoea was the most serious symptom.The study has identified CCT, viz . its saponins content, as a promising plant with acute and broad rodenticidal activity.     الحنظل Citrullus colocynthis (L.) Schrad من النباتات الطبية المهمة المنتمية للعائلة القرعية، وهو معروف في الطب الشعبي في الأرياف بوصفه مادة مسهلة وفي علاج داء السكري ومبيداً حشرياً. هدفت هذه الدراسة إلي  تقويم سمية صابوينات ثمار هذا النبات. تم اختبار السمية الحادة للصابونينات المستخلصة من قشور ثمار نبات الحنظل عليطريق الحقن عبر الغشاء البريتوني للجرذان النرويجية البهقاء Berkenhout)) Rattu norvegicus . بناءً على تجارب أولية تم اختبار خمس جرعات وهى 60 ، 70، 80، 90 و 100 مجم صابونين خام / جرذ .خضعت الجرذان المعاملة والشاهد للملاحظة لمدة (96) ساعة لتحديد علامات (أعراض) السمية الحادة للمستخلص ماتت الجرذان خلال 1– 4 أيام  من المعاملة. وكانت النسبة المئوية المصححة للموت كالآتي: صفر، 25، 50 ،         75 و100 للجرعات المذكورة أعلاه بالترتيب. التركيز القاتل النصفي  LC 50 عن طريق تحليل الاحتمالات (البروبيت) كان حوالي 43 .79مجم /جرذ. تمثلت علامات السمية الحادة في الفقدان الكامل للشهية ، الارتجاف ، صعوبة التنفس ، عدم المقدرة علي الوقوف ، انسدال جفون العين مع بعض الإفرازات ، النزيف وأخطرها كان الإسهال الحاد ثم  الانهيار التام والموت. اثبتت هذه الدراسة أن الحنظل ممثلاً في الصابونينات المستخلصة منه نباتاً واعدا يمكن استخدامه في مكافحة القوارض.